ANÃLISE ESPACIAL DA MOSCA-NEGRA-DOS-CITROS EM POMAR DE CITROS UTILIZANDO A GEOESTATÃSTICA - Silva, Anderson GonÃ§alves da; Farias, Paulo Roberto Silva; BoiÃ§a Junior, Arlindo Leal; Correia, Rui Guilherme; Silva, Juliana Barroso da; Rodrigues, Nara Elisa Lobato (REVISTA DE AGRICULTURA, 2016)
ANÃLISE ESPACIAL DA MOSCA-NEGRA-DOS-CITROS EM POMAR DE CITROS UTILIZANDO A GEOESTATÃSTICA